The Negative Impact Of Employee Perceived (Hpws) On Employee Creativity As Related To Organizational Performance In Kurdistan - Baderkhan Abdulla Omer; Shirzad Mohammed Mahdi (QALAAI ZANIST JOURNAL, 2020)
Aim & Background: high performance work system (HPWS) plays an important role in management practice. However, evidence of its practice shows that there are impacts on the employee performance and creativity of the individual within the organization. This study investigates the role of job tenure and role overload in determining the effects and relations between high performance work system (HPWS) and employee creativity. Methods: The present study was accomplished in 15 public and private institutions in Erbil city of Iraq, from August 2019 to December 2019. The data collection instrument was a questionnaire including 23 items. The sample of the study included 139 employees in different levels in the selected institutions. Hypotheses were tested and analyzed statistically using SPSS software. Results: findings show that there is positive and significant effects and the correlation between HPWS, employee creativity, and role overload, this indicates that role overload positively mediates the relationship between employee perceived HPWS and employee creativity. in addition, the results indicate that employee job tenure negatively moderates the relationship between employee perceived HPWS and employee creativity. Research limitations– the research limit generalizability of the findings because the data collected in Erbil city of Iraq and each cities has its own unique environment. Future studies can extend these findings by conducting studies in other societal contexts.